ALFRED SCHNITTKE’S POLYSTYLISTIC JOURNEY: “THE THIRD STRING QUARTET” - Oana ANDREICA (Studia Universitatis Babeş-Bolyai. Musica)
Within the extremely eclectic musical manifestations of the 20th century, Alfred Schnittke stands as a key‑figure, being one of the most influential composers to have linked the past to the present, creating an original sound world, tormented by violent contrasts and conflicts, confusion, nostalgia, irony and parody. His works often look back at the musical tradition, exploring its potential by means of modern compositional techniques and thus giving it a totally new shape and value. Often associated with the postmodern orientation, Alfred Schnittke is the exponent of the complex concept of polystylism, bringing the idea of borrowings of musical material to a superior level. Integrating them into the organic structure of his works and subjecting them to variation up to the loss of their identity, they receive a double significance: on the one hand, they represent testimonies of an ancient world, on the other elements that symbolize the ever changing contemporary musical scenery.